Optimasi Pemutuan Ikan Patin Asap Secara Non Destruktif dengan Jaringan Syaraf Tiruan (State Of The Art) - Saputra, Edo; Sirait, Sudirman; Tri Suci, Yunisa (Balai Pelatihan Pertanian Jambi, 2023)
Catfish (Pangasius hypothalamus) is the most widely cultivated fishery commodity which can be sold in fresh form. In addition, catfish can also be processed into smoked catfish so that it has a higher selling value. Smoked catfish usually arrives abroad such as Malaysia, but currently it has stopped because the shelf life of smoked catfish can only last for 14 days. Currently, physical quality identification of smoked catfish is done manually and chemical quality is done destructively. Efforts are needed to determine smoked catfish using artificial intelligence such as image processing, artificial neural networks, and near infrared (NIR). This method has been widely used in identifying the physical and chemical properties of fresh and livestock fishery products and processed products from each. This state of the art aims to describe the development of fishery and livestock product quality control technology that is currently being developed, specifically in image processing, artificial neural networks, and NIR which are used to identify the physical quality and chemical content of fishery and livestock products and their processed products